2018
DOI: 10.11604/pamj.2018.29.8.13239
|View full text |Cite
|
Sign up to set email alerts
|

The physician-scientists: rare species in Africa

Abstract: There is paucity of physician-scientists in Africa, resulting in overt dependence of clinical practice on research findings from advanced “first world” countries. Physician-scientists include individuals with a medical degree alone or combined with other advanced degrees (e.g. MD/MBChB and PhD) with a career path in biomedical/ translational and patient-oriented/evaluative science research. The paucity of clinically trained research scientists in Africa could result in dire consequences as exemplified in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 25 publications
1
24
2
Order By: Relevance
“…The shortage of physician scientists and the potential consequences were highlighted by the commentary of Adefuye, Adeola and Bezuidenhout [16]. One thing that should be added to this is the need to provide quality supervision in all relevant fields.…”
Section: Variants Of Doctorates In Bms and The African Scenariosmentioning
confidence: 99%
“…The shortage of physician scientists and the potential consequences were highlighted by the commentary of Adefuye, Adeola and Bezuidenhout [16]. One thing that should be added to this is the need to provide quality supervision in all relevant fields.…”
Section: Variants Of Doctorates In Bms and The African Scenariosmentioning
confidence: 99%
“…The clinical workload and high need for service delivery in most parts of Africa and, indeed, the Free State province, often make it difficult if not impossible for healthcare professionals to dedicate time to self-professional development (30,31). This inability may be the case for those EMCPs (16.3%) who reported that they do not have the time to read scientific journals ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The urgent need for these professionals became even more apparent during and after the epidemic. 5 , 7 , 8…”
Section: Introductionmentioning
confidence: 99%
“…Globally, declining numbers and activities of physician-scientists over the years, especially in Africa, have been reported [1][2][3][4][5] These scientists complement other researchers in the health sciences and have contributed to the recent advances in medicine which have improved the quality of life and life expectancy globally. By definition, physician scientists are medical graduates with an interest in basic science or clinical research including translational and patient-oriented research as well as the evaluative sciences, who perform this as their primary professional activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation